RESHAPING EU STATE AID POLICY AMID GREEN TRANSFORMATION AND GEOPOLITICAL TENSIONS - ANDREEA - EMANUELA DRĂGOI; ANCA DRAGOMIR (Global Economic Observer, 2025)
State aid policy represents a cornerstone of the European Union’s (EU) free and competitive internal market. While its traditional aim was to prevent unlawful competition and the unfair advantage of large companies, recent years—marked by successive crises beginning with the pandemic and followed by the disruptions caused by the war in Ukraine—have brought major transformations to this policy. The most significant shift is the emergence of state aid as a key instrument for mitigating the economic shocks experienced by Member States, allowing national authorities to provide targeted support across all economic sectors. Special legal derogations, such as the Temporary Framework and the Temporary Crisis Framework, have facilitated this change, enabling substantial volumes of aid to be granted across the EU. Against this backdrop, our research pursues two objectives: first, to highlight the major regulatory transformations in state aid policy in response to recent economic and geopolitical challenges; and second, to assess—through a comparative analysis of aid granted by different Member States—whether the policy still upholds its central goals of fostering a competitive and green economy while preserving free competition within the EU internal market. Methodologically, we adopt a mixed approach, combining an in-depth literature review and a qualitative analysis of the most recent legal frameworks with a statistical examination of relevant state aid measures implemented during the post-pandemic period, using the latest available State Aid Scoreboard data. Our main finding underscores that, while facilitating economic recovery, state aid policy has also supported green development by promoting sustainable and clean growth across the EU.